Dynamic investigation of centralized and decentralized storage systems for a district heating network. (10th December 2022) - Bellos, Evangelos; Iliadis, Petros; Papalexis, Christos; Rotas, Renos; Nikolopoulos, Nikos; Kosmatopoulos, Elias; Halmdienst, Christian
Abstract: District heating is an efficient and promising way to cover the residential space-heating and domestic hot water needs, resulting in economic and environmental benefits, especially if operated by renewable power stations, when compared to fossil fuels. In this direction, the present study investigates in detail a district heating network with novel decentralized storage for domestic hot water (enerboxx scenario), over centralized storage systems, applying a specific schedule-based approach for the coordinated hot water tank charging. The goal of this design is to properly control the system by charging it at predetermined time periods during the day aiming at i) diminishing the thermal losses and ii) reducing the thermal demand from the grid, over the period of a day. The simulation is conducted with a newly developed component-based tool, called INTEMA, which is based on the Modelica language. This encompasses the ability to discretize with high temporal resolution and adjustable time steps the overall grid configuration, with the support of customizable level of detail models for simulating key system components such as the storage tanks, the piping and the dwelling needs, as well as the application of an advanced control system over the district heating network and the dwellings. More specifically, a combined control system that controls both operating parameters in the network and inside the dwellings is applied. The developed system model is verified against available data for a standard centralized storage system (reference scenario) and afterwards, the novel decentralized design is compared against corresponding results of the standard system, as concerns key operational parameters; indicatively the temperature levels of the hot water and the heat load demand. The analysis is conducted for a heating network of 9 dwellings in Austria, which have an underfloor heating system, a system for covering the domestic hot water demand, considering also that each of these 9 dwellings is characterized by a unique demand profile. It was found that the decentralized approach leads to lower demand and there are energy savings of 18 % compared to the reference scenario, while the thermal losses are reduced by about 22 %. Moreover, a parametric study regarding the storage tank volume and the heat exchanger thermal transmittance in the tank is conducted, in order to examine the impact of these design parameters on the system dynamic behavior. Highlights: Centralized and decentralized district heating networks are compared. A new tool for simulating district heating systems is developed in Modelica language. The analysis is a detailed dynamic investigation regarding 9 dwellings in Austria. The developed models were validated with provided data by the manufacturer. The decentralized storage system leads to 18 % energy savings on a yearly basis.